Institutionalization, Organizational Commitment, and Hope for Personal Fulfillment in The Shawshank Redemption - Lin, Chia-Li; Wang, Ya-huei (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
Institutionalization is a socialization process through which the values, beliefs, policies, and practices of an organization are instilled within the members of that organization that they might collectively adopt these values or rules and commit themselves to that organization. However, those being institutionalized under authoritarian discipline may lose the freedom of their soul and a personal level of self. In order to raise readers’ awareness of the impact of institutionalization and commitment on the individual or collective actors, this study intends to use the film The Shawshank Redemption as a case study, using content analysis as a qualitative research technique to analyze the symbolic scenes in the film in order to reveal how commitment and stability via institutionalization can be brought into the organization. To achieve this goal, the study uses Scott’s institutional theory and Meyer and Allen’s organizational commitment model to demonstrate how commitment may greatly impact people. Those being institutionalized, like Brooks in The Shawshank Redemption, may lose their ability to think and act independently and thus lose their hope for fulfillment. However, those like Andy and, later, Red, choosing to hold on to freedom of the soul and a personal level of self, can deinstitutionalize themselves; break free of the shackles, either physically or spiritually, of the organization; and make a commitment toward their own inner development.